Pengaruh Budaya Organisasi dan Disiplin Kerja terhadap Kinerja Pegawai Melalui Kepuasan Kerja sebagai Variabel Intervening pada Biro Administrasi Pimpinan di Kantor Gubernur Provinsi Sumatera Barat - Shilpa Nurhaliza; Selvi Yona Sari; Hilda Mary (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This research aims to determine and attempt to analyze the influence of organizational culture and work discipline on employee performance through job satisfaction as an intervening variable at the West Sumatra Province Governor's Lead Administration Bureau. This research is a Structural Equation Modeling (SEM) model with the SmartPLS 3.0 analysis tool. The population and sample for this study were employees of the West Sumatra Province Governor's Leadership Administration Bureau. The research results found that there was a negative and insignificant influence between organizational culture on job satisfaction. There is a positive and significant influence between organizational culture on employee performance. There is a positive and significant influence between work discipline and job satisfaction. There is a positive and significant influence between work discipline on employee performance. There is a positive and significant influence between job satisfaction and employee performance. Job satisfaction is not able to mediate organizational culture on employee performance. Job satisfaction is able to mediate work discipline on employee performance.